(3bhI GdYbd GdCShOs - (3YHO GdYGd, eMeOs; (3GdfhHj, jSQGs; (3ShGM, SGde YHO GdeYRs ((3GdbGgQIs (3OGQ RMeI cJGH ddfTQ hGdJhRjYs, 2025)
(3GdbhI GdMbjbjI Jcef aj eYQaI NHGjG GdfaS GdHTQjI hGdhYj HfaSc gh eaJGM GdJMQQ ef GdJdGYH GdfaSj ef bHd GdHTQ aEf cTa GdNaGjG GdfaSjI ddHTQ gh WQjbc ddfLGI ef JdGYHge GdfaSj hcPdc aEf GdhYj HJCKjQ GdBNQjf hage OhGaYge gh OQYc GdhGbj dMeGjJc ef GdJdGYH GdfaSjs
Keywords: (3GdUMI GdfaSjIs; (3GdYbds; (3GdYdGbGJ GdEfSGfjIs; (3GdfLGM GdTNUjs